Improved column generation algorithm for disrupted airline schedules recovery - Wu, Gang; Yan, Jun (Nanjing hang kong hang tian da xue xue bao, 2014)
The disrupted airline schedules caused by the shortage of aircraft resources is considered as a multi-commodity integer minimum cost flow with the side constraints, and a mathematic model of multi-commodity network flow is established. The column generation scheme is introduced to solve the integer programming problem. Generally, only one column is added in each iteration for the column generation algorithm, which results in excessive number of iterations, thereby reduces the efficiency of the algorithm. The method of adding more columns in each iteration process is set up, and the requirements which the added multiple columns should meet are analyzed. Finally, an example is given to validate the correctness and efficiency of the method.